Exercise Immunology Applied to Pediatric Sport and the Importance of Monitoring Stages of Puberty and Biological Maturation - Almeida-Neto, Paulo Francisco de; de Medeiros, Jason Azevedo; Jaggers, Jason R.; Ferreira, Ayrton Bruno de Morais; de Assis, Gilmara Gomes [UNESP]; Cabral, Breno Guilherme de Araújo Tinôco; Dantas, Paulo Moreira Silva (SAGE Publications, 2023)
Context: Exercise immunology is aimed at understanding how exercise sessions can affect the immune system in athletic subjects of different age groups. The objective of the current study was to discuss in which stage of biological maturation (BM) young athletes may be more vulnerable in relation to the immune system, and whether there is a BM range in which it is safer to perform sports training with strenuous exercise loads. Evidence Acquisition: Evidence from scientific research from several scientific disciplines (eg, immunology, sport immunology, pediatrics, sports medicine, human development) was gathered to holistically examine the main particularities of exercise immunology as applied to pediatric sport. Study Design: Narrative review. Level of Evidence: Level 5. Results: In pediatric patients, lymphoid tissue expands during puberty and involutes after puberty until it returns to pre-expansion values. This suggests that there is a specific period in which the immune system may be stronger, which may provide opportunities for strenuous exercise in pediatric athletes. However, the chronological period when puberty occurs will be determined by BM, which is the rate at which the biological systems of the human body improves. This may affect the period of lymphoid tissue expansion and, consequently, the behavior of the immune system in pediatric subjects of the same age category. Conclusion: During puberty, there is a significant increase in the proinflammatory profile; to compensate for this, there is an expansion of lymphoid tissue that may favor the efficiency of the immune system. The period in which puberty is reached may vary according to the stages of BM. Therefore, in exercise immunology applied to pediatric sports, in addition to external and internal training loads, it is necessary to consider BM and puberty, which have been shown to be safer biomarkers than chronological age for determining immune system behavior in pediatric athletes. Strength-of-Recommendation Taxonomy (SORT): Evidence B level 3.
Keywords: adolescents; immune system; maturity; open window; training load